Branding Strategies for Strengthening the Identity of Islamic Higher Education Institutions - Arsyadana, Addin; Indrioko, Erwin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to examine how Islamic Religious Higher Education Institutions (PTKI) maintain their Islamic identity and institutional character amid the currents of digitalization and global competition through the implementation of brand image strategies. This research uses a qualitative case study approach, employing observation, interviews, and document analysis. The results indicate that PTKI successfully built a brand image by constructing a unique institutional narrative with distinct characteristics, strengthening networks through leaders, lecturers, and alums, and optimizing the use of digital media for communication and to broaden the institution's awareness. Furthermore, a comprehensive evaluation was conducted to assess the strategy's effectiveness. The findings of this study emphasize the importance of PTKI actively adapting to the demands of the times, without losing its ideological roots and traditional values. The implications of this research broaden the understanding of the application of brand image strategies in building institutional image, as well as the role of public networks in strengthening the existence of higher education in the digital era.